Criteria used in setting the English language component of the mature students' entrance examination questions in Ghana - Asafo-Adjei, Ramos; Klu, Ernest Kwesi; Bukari, Francis (Technium Social Sciences Journal, 2022)
The centrality of examinations to the understanding of competences and abilities of examinees across the globe cannot be overemphasised. The paper focused on exploring the criteria used in setting the English language component of the Mature Students’ Entrance Examination questions in Ghana. The qualitative design (specifically, multiple case study design) was employed for the paper. Using the multi-stage sampling technique, five Ghanaian universities were used for the paper. The data was elicited from in-depth interviews applied on the lecturers who set the English language component of the MSEE questions. [1] data analysis spiral plan was employed to analyse the data. The paper revealed that there were major weaknesses in the criteria used by the universities in areas such as training of the assessors, use of standard assessment models and consideration of test takers’ characteristics. The paper advanced, to policy makers, suggestions such as the adoption of standard assessment models and the training of the assessors for the improvement of the examination2